Aflatoxin biocontrol effectiveness in the real world—Private sector-led efforts to manage aflatoxins in Nigeria through biocontrol-centered strategies - Ola, O. T.; Ogedengbe, O. O.; Raji, T. M.; Eze, B.; Chama, M.; Ilori, O. N.; Awofisayo, M. A.; Kaptoge, L.; Bandyopadhyay, R.; Ortega-Beltran, A.; Ndarubu, A. A. (Frontiers in Microbiology, 2022)
Aflatoxins are toxic compounds produced by several Aspergillus species that contaminate various crops. The impact of aflatoxin on the health of humans and livestock is a concern across the globe. Income, trade, and development sectors are affected as well. There are several technologies to prevent aflatoxin contamination but there are difficulties in having farmers use them. In Nigeria, an aflatoxin biocontrol product containing atoxigenic isolates of A. flavus has been registered with regulatory authorities and is now being produced at scale by the private company Harvestfield Industries Limited (HIL). The current study reports results of biocontrol effectiveness trials in maize conducted by HIL during 2020 in several locations across Nigeria and compared to untreated maize from nearby locations. Also, maize was collected from open markets to assess levels of contamination. All treated maize met tolerance thresholds (i.e., < 4 ppb total aflatoxin). In contrast, most maize from untreated fields had a higher risk of aflatoxin contamination, with some areas averaging 38.5 ppb total aflatoxin. Maize from open markets had aflatoxin above tolerance thresholds with even an average of up to 90.3 ppb. Results from the trials were presented in a National Workshop attended by key officers of Government agencies, farmer organizations, the private sector, NGOs, and donors. Overall, we report i) efforts spearheaded by the private sector to have aflatoxin management strategies used at scale in Nigeria, and ii) deliberations of key stakeholders to ensure the safety of crops produced in Nigeria for the benefit of farmers, consumers, and industries.